Hepatitis E Virus (HEV) in Heavy Pigs in Slaughterhouses of Northern Italy: Investigation of Seroprevalence, Viraemia, and Faecal Shedding - Marina Monini; Ilaria Di Bartolo; Luca De Sabato; Giovanni Ianiro; Francesca Agostinelli; Fabio Ostanello (Animals, 2023)
Hepatitis E virus (HEV) is considered an emerging threat in Europe, owing to the increased number of human cases and the widespread presence of the virus in pigs at farms. Most cases in industrialized countries are caused by the zoonotic HEV-3 genotype. The main transmission route of HEV-3 in Europe is foodborne, through consumption of raw or undercooked liver pork and wild boar meat. Pigs become susceptible to HEV infection after the loss of maternal immunity, and the majority of adult pigs test positive for IgG anti-HEV antibodies. Nonetheless, HEV-infected pigs in terms of liver, faeces, and rarely blood are identified at slaughterhouses. The present study aimed to investigate the prevalence of HEV-positive batches of Italian heavy pigs at slaughterhouses, assessing the presence of animals still shedding HEV upon their arrival at the slaughterhouse by sampling faeces collected from the floor of the trucks used for their transport. The occurrence of viraemic animals and the seroprevalence of anti-HEV antibodies were also assessed. The results obtained indicated the presence of anti-HEV IgM (1.9%), and a high seroprevalence of anti-HEV total antibodies (IgG, IgM, IgA; 89.2%, n = 260). HEV RNA was not detected in either plasma or faecal samples. Nevertheless, seropositive animals were identified in all eight batches investigated, confirming the widespread exposure of pigs to HEV at both individual and farm levels. Future studies are needed to assess the factors associated with the risk of HEV presence on farms, with the aim to prevent virus introduction and spread within farms, thereby eliminating the risk at slaughterhouse.